A Dene First Nation's community readiness assessment to take action against HIV/AIDS: a pilot project. Issue 1 (1st January 2019) - Larcombe, Linda; McLeod, Albert; Samuel, Sarah; Samuel, Jennifer; Payne, Michael; Van Haute, Stephanie; Singer, Matthew; Ringaert, Laurie; Meyers, Adrienne F. A.; Kinew, Kathi; Keynan, Yoav; MacDonald, Kelly; et al.
ABSTRACT: Background: Among Indigenous people in Canada the incidence of HIV is 3.5 times higher than other ethnicities. In Manitoba First Nations, Metis and Inuit people are disproportionately represented (40%) among people who are new to HIV care. Northlands Denesuline First Nation (NDFN) identified the need to revisit their level of knowledge and preparedness for responding to the increasing rates of HIV. NDFN piloted a community readiness assessment (CRA) tool to assess its appropriateness for use in northern Manitoba. Methods: A First Nation and non-First Nation research team trained to administer the CRA tool at NDFN in Manitoba. Five informants were interviewed using the CRA tool and the responses were scored, analysed and reviewed at community workshops and with stakeholders to develop a 1-year action plan. Results: CRA training was best conducted in the community. Using the readiness score of 2.4 along with feedback from two workshops, community members, the research team and stakeholders, we identified priorities for adult education and youth involvement in programmes and planning. Conclusions: In response to the increasing incidence of HIV, a northern First Nation community successfully modified and implemented a CRA tool to develop an action plan for culturally appropriate interventions and programmes.